The intensity of the research activities on e learning for care givers of autistic children - Shminan, A.S.; Norsiah, Fauzan; Aren, M. (2016)
Autism, known as a spectrum disorder (ASD) is seen in early childhood or by three years of age. ASD is a neuro-developmental disorder characterized by deficits in social responsiveness, impairments in verbal and nonverbal communication. The purpose of this paper is to demonstrate the relevance of e-learning technology to the area of training the caregivers of autistic children. Our search focused on a number of data banks that contain numerous references to autism and home based treatment. Our results found only ten papers published since 2010 that met our criteria for inclusion. Six were demonstrations of e learning to teach caregivers and professionals the basics of applied behavior analysis and some techniques for skill training. The remainder of the studies fell into the telehealth category which involved direct communication between a professional and caregiver in the home. The studies suggest that home based service delivery is effective and offers both the social service system and parents considerable financial savings. The use of Web based platform (e learning and telehealth) is depicted as an aid to caregivers of autistic children. The need for more studies of the variables related to home based service delivery is noted.